STUDI KOMPARATIF PRODUKSI DAN PENDAPATAN AGROINDUSTRI GULA KELAPA UKURAN KECIL DAN UKURAN BESAR (STUDI KASUS DI DESA SUMBERASRI KECAMATAN NGLEGOK KABUPATEN BLITAR) - Sofya, Zahrit; Sudiyarto, Sudiyarto; Waliulu, A. Rachman (Berkala Ilmiah AGRIDEVINA, 2017)
The coconut sugar agroindustry located in Sumberasri Village of Blitar Regency is thehousehold scale industry. Initially, the coconut sugar producers in Sumberasri village ofBlitar Regency only produced the large size coconut sufar, but in the growth the coconut sugar consumers, in particular in Blitar regency, went into the change of taste inconsuming coconut sugar, a part of consumers assessed that the coconut sugar with smallsize is more practical and efficient. This case encourage coconut sugar producers toproduce the small size coconut sugar for the sake of satisfying the consumer demands.This research has the purposes, namely: To identify the characteristics of the producersof the small size and large size coconut sugar in Sumberasri village Nglegok subdistrictBlitar regency, To identify the reasons of coconut sugar producers to produce the smallsize and large size coconut sugar, To analyze the production cost and income of smallsize and largse size coconut sugar in Sumberasri village Nglegok subdistrict Blitarregency. The research location was in Sumberasri village Nglegok subdistrict Blitarregency with, research objects were coconut sugar producers, research respondents were4 small size coconut sugar producers and 8 large size coconut sugar producers. Based onthe results and discussion obtained that coconut sugar producers produced coconut sugarin 7 workdays with the amounts of small size coconut sugar were 410 kg and for the largesize coconut sugar were 233.5 kg. Whereas, the amounts of average income of the smallsize coconut sugar were Rp. 1,005,651.855 and the large size coconut sugar were Rp.284,685.66, this case obviously different in the production and income of the small sizeand large size coconut sugar.